KONTRIBUSI KONSENTRASI DAN POWER OTOT TUNGKAI TERHADAP HASIL TENDANGAN PENALTY PADA SISWA PUTRA EKSTRAKULIKULER FUTSAL MTS AL IKHLAS TANJUNG BINTANG - Yusuf Fajar Damayono; Heru Sulistianta; Joan Siswoyo; Dwi Priyono (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
This study aims to determine the contribution of concentration and leg muscle power to the results of penalty kicks among male extracurricular futsal students at MTs Al Ikhlas Tanjung Bintang, both individually and collectively. This research is correlational research. The subjects of this research were male students who took part in the futsal extracurricular at MTs Al Ikhlas Tanjung Bintang in the 2023–2024 academic year, totaling 25 students. The data analysis technique uses product moment correlation analysis and the coefficient of determination to find the magnitude of the contribution, as well as prerequisite tests for normality and linearity. The research results showed that there was a significant contribution between concentration on penalty kicks the contribution amount was 27.6%; there is a significant contribution of leg muscle power to penalty kicks the contribution amount is 54.0%. There is a significant contribution between concentration and leg muscle power on penalty kicks a contribution of 54.3%.